Pengembangan Media Komik pada Materi Metamorfosis Kelas III SD Negeri 08 Sungai Raya - Astuti, Windiani; Setyowati, Dessy; Bawamenewi, Arozatulo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low interest in reading among students, which is caused by the limited variety of learning media used in schools. The purpose of this study was to develop and produce learning media in the form of metamorphosis comics that are suitable for use by third-grade elementary school students. This study was a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation process was carried out by media experts, subject matter experts, language experts, and education practitioners. The results of the data analysis showed that the assessment by media experts obtained a feasibility percentage of 88% (highly valid), subject matter experts 80% (valid), language experts 92% (highly valid), and practitioners 99% (highly valid). Individual trials showed a result of 94.4% (highly valid). Based on these results, the metamorphosis comic learning media was declared highly valid and suitable for use in learning activities in Year 3 of primary school.